DEVELOPING 'KIBAFLO' FLIPBOOK AS CANVA & BOOK CREATOR-BASED INTERACTIVE LEARNING MEDIA FOR 3RD GRADERS ON THE BATTLE OF BADR - Fitri, Alfia Nur; Rahmawati, Revy Trisely; Mariska, Nova; Nur Aeni, Ani (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2025)
Digital technology is rapidly advancing, making communication and information access more convenient. This progress is also impacting teaching and learning, making education more efficient and accessible from anywhere. Learning becomes more effective with the appropriate use of learning media. Digital technology helps make learning media more accessible. This study aims to create an interactive digital flipbook titled